Induction of Synthesis of Plasminogen Activator Inhibitor Type-1 byTissue-Type Plasminogen Activator in Human Hepatic and Endothelial Cells - Fujii, Satoshi; Lucore, Charles L; Hopkins, William E; Billadello, Joseph J; Sobel, Burton E (Thrombosis and Haemostasis, 1990)
Plasminogen activator inhibitor type-1 (PAI-1) can modify fibrinolytic activity in vitro and in vivo. The present study was performed to determine whether pharmacologic concentrations of tissue-typeplasminogen activator (t-PA) can initiate negative feedback by stimulating PAI-1 synthesis. In both human hepatoma cells (Hep G2) and human umbilical vein endothelial cells (HUVEC), t-PA increased the total concentrations and appearance of newly synthesized protein inconditioned media of free PAI-1 and PAI-1 complexed with t-PA in a dose and time dependent fashion judging from results after immunoprecipi-tation of metabolically labeled PAI-1. The t-PA effect was not attributable simply to release of stored or matrix-bound PAI-1. In HUVEC, Northern blot analyses indicated that t-PA increased steady-state levels of PAI-1 mRNA two-fold. In contrast PAI-1 mRNA expression was not increased in Hep G2 cells. Thus, mechanisms of stimulation appeared to differ in the two cell lines. The results obtained are consistent with the hypothesis that increased PAI-1 synthesis and secretion in response to t-PA may limit or attenuate fibrinolysis locally or systemically in vivo.